The Impact of the Implementation of Solvency II on the Financial Reporting of Insurance Companies in Poland - Chmielowiec-Lewczuk, Magdalena (Studia Oeconomica Posnaniensia, 2016)
In view of the changing conditions of the financial market, there is a need to change the tools for assessing the financial condition of insurers. This is why, for several years, the researcher carried out preparatory work which will lead to the implementation of the European insurers’ project, called Solvency II, in 2016. This project is intended primarily for the supervisory authorities of the insurance market for more effective control, and thus also can indirectly better protect customers of insurance services. The implementation of the Solvency II project entails a substantial modification of the scope of the accounting information. On the other hand, in Poland, there is domestic legislation of accounting, which is not always harmonized with Solvency II. This paper presents an analysis of the scope of information that is required when preparing reports for supervision, i.e. Solvency II and in the financial statements prepared according to Polish accounting law.